FIGURE 4 in Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica) - Peña Cantero, Álvaro L. (Zenodo, 2021)
FIGURE 4. Oswaldella vervoorti Peña Cantero & García Carrascosa, 1998 (Holotype): A, cauline apophysis and first forked hydrocladial internode (arrow pointing to hydrocladial apophysis), B, distal part of a forked hydrocladial internode showing hydrotheca, hydrocladial apophysis and nematophore (arrow); C, first unforked hydrocladial internode (centre) following hydrocladial apophyses; D, unforked hydrocladial internodes; E–F, cauline apophyses showing mamelon (arrows). Scale bar: 100 µm (B, E–F), 200 µm (A, C–D). : Published as part of Peña Cantero, Álvaro L., 2021, Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica), pp. 321-336 in Zootaxa 4966 (3) on page 334, DOI: 10.11646/zootaxa.4966.3.4, http://zenodo.org/record/4736691